Dynamic Relationship between Monetary Policy and Economic Growth (Global Journal of Human-Social Science, 2019)
This study investigated the dynamic relationship between monetary policy on economic growth in Nigeria. Data for the study were collected from secondary sources. The variables on which data are collected include; real GDP, Broad money supply (BMS), Cash reserves ratio (CRR), Monetary policy rate (MPR), Liquidity ratio (LQR). The scope of the study covers the period from 1986 to 2017 and were sourced from CBN statistical bulletin. Data are analysed using the descriptive statistics and ordinary least square regression, Johansen cointegration, VECM and granger causality approach. Findings revealed that CRR and BMS have inverse long run relationship with GDP MPR and LQR exert positive long run relationship with GDP. In the short run CRR and MPR had an inverse relationship with GDP at lag while LQR exerts positive relationship with GDP. Using granger causality, RGDP and BMS, MPR, and CRR has no causal relationship between while and NQR exerts significant cause on Real GDP. From the findings, the study recommends that the policy instrument should be a well-coordinated optimal mix of instruments to significantly influence economic stability.
Keywords: monetary policy; real gdp; cointegration; VECM